The Development of E-Worksheet as Interactive Instructional Media for Teaching Reading Recount Text at X Grade - Aurelia Fitria Zahra; Indah Tri Purwanti; Novitri Novitri; Zaldi Harfal (FKIP - Universitas Riau, 2026)
This research focuses on developing an interactive E-Worksheet for teaching reading recount text to X Grade students, addressing challenges in traditional learning methods. Under the Merdeka Curriculum, technology-based instructional resources are essential since traditional teaching methods frequently fall short in terms of properly engaging students. In order to improve student learning and engagement, the study intends to develop and validate an e-worksheet using the Liveworksheets platform. This study employs a Research and Development (R&D) methodology that excludes Implementation, based on the ADDIE paradigm (Analysis, Design, Development, and Evaluation). After conducting a needs analysis using teacher interviews and student questionnaires, the findings were verified by experts in the fields of pedagogy, media, and materials. The designed E-Worksheet has validation ratings of 3.52 for media, 3.95 for material, and 3.79 for pedagogical elements, indicating that it satisfies high validity standards. Learning becomes more interesting and useful when interactive elements like activities, audio, and videos are incorporated. In conclusion, the developed E-Worksheet is a useful resource for raising learning objectives and reading comprehension in the recount text. By providing a modern and innovative student-centered learning resource that satisfies curricular requirements and boosts enthusiasm in reading activities, this research advances educational technology.